163 EVALUATING THE ROLE OF THE GERIATRIC DAY HOSPITAL IN MEDICATION OPTIMISATION. (18th November 2021) - Lynch, A; Quinn, L; Briggs, R; Tan, T; Thorpe, O; Romero-Ortuno, R; Byrne, T; Cunningham, C; Lavin, A
Abstract: Background: The geriatric day hospital (GDH) provides outpatient geriatric medical, nursing and rehabilitation care to older adults. The aim of this study was to assess whether medication optimisation occurs in this setting. We believe the GDH would be an ideal location for mediation optimisation due to the stable community dwelling patients and close follow up by specialised physicians. Methods: Electronic patient records of the new patients ≥65 years seen in the GDH over a 3-month period were reviewed. Potentially inappropriate prescriptions (PIPs) and potentially prescribing omissions (PPOs) were identified using the STOPP/START prescribing tool on admission to the GDH and again at discharge from the GDH. Results: One-hundred and sixty-seven patient records were reviewed; mean age 80.8 (SD6.5) years, 62.9% female, median clinical frailty scale score 6 (IQR5–6), mean number of conditions 5.79 (SD3), mean number of medications 7.57 (SD3.7). Patients had a median of 4 (IQR2–7) consultations. The number of patients prescribed at least 1 STOPP-PIP reduced by 10% (42.4% vs 38%; p < 0.001). Vasodilator drugs in patients with orthostatic hypotension were deprescribed most frequently (6.5% vs 3%; p < 0.001). PPOs were reduced by 36% (47.5% vs 30.6%;p < 0.001). The largest improvement was identified in the prescription of vitamin D in patients experiencing falls (17.4% vs 13.8%;p < 0.001). Logistic regression was performed to ascertain the influence of age, gender, falls, dementia, co-morbidity number and medication number on the likelihood of a patient experiencing a PIP or PPO. For every medication prescribed, the odds of experiencing a PIP increased by 11.8% (OR1.187, 95%CI 1.052–1.339). Being female increased the odds of experiencing a PPO by 21.7% (OR2.17, 95%CI 10.53–4.468). Conclusion: Medication optimisation is key in avoiding side effects from potentially inappropriate medications. The frequency of patient attendances coupled with geriatricians' expertise makes the GDH an ideal setting for medication optimisation in multi-morbid frail community-dwelling older adults.